Otimização da aplicação de Fluazifop-P-Butil em pós-emergência na cultura de soja (Glycine max) - Lima, P.r.f. [UNESP]; Machado-neto, J.g. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2001)
The objective of this study was to evaluate the possibility of reducing spray concentration and volume of Fluazifop-p-butyl applications on postemergence soybeans, while maintaining weed control and growth selectivity. The study was conducted in the experimental area of the Teaching and Research Farm of FCAV/Unesp - Jaboticabal Campus, during the agricultural season of 1998/99, carried out on a crop of soybean cultivar FT 2009. The experimental setup utilized was a randomized block design with 24 treatments, 20 following a factorial scheme 2 x 2 x 5 and 4 control treatments. The factors examined were: spray volume (100 and 200 L ha-1); reduced spray concentration - 75.2 and 112.8 g of fluazifop-p-butyl/ha (40 and 60% of the recommended concentration, respectively); and application schedule (5 A.M., 9 A.M., 1 P.M., 5 P.M. and 9 P.M.). The controls were applications at the recommended concentration (188.0 g fluazifop-p-butyl/ha), using volumes of 100 and 200 L ha-1, and treatments without weed control and weeds controlled with manual hoeing. The main species of weeds that emerged in the experimental area were: Cenchrus echinatus, comprising 60% of the infested sections; Digitaria horizontalis, 10%, and Eleusine indica, 30%. All fluazifop-p-butyl applications made up to 9 A.M. and from 5 P.M. effectively controlled the three species of weeds and provided a selective growth of soybeans. Therefore, the use of fluazifop-p-butyl can be optimized by reducing both the concentration and the volume of the spray for applications times providing favorable conditions for crop dusting.

O objetivo deste trabalho foi avaliar a possibilidade de redução da dosagem e do volume de calda em função do horário de aplicação do herbicida fluazifop-p-butil em pós-emergência na cultura de soja, mantendo-se o controle das plantas daninhas e a seletividade para a cultura. O experimento foi conduzido na área experimental da Fazenda de Ensino e Pesquisa da FCAV/UNESP - Jaboticabal, no ano agrícola 1998/99, na cultura de soja, cultivar FT 2009. O delineamento experimental utilizado foi o de blocos ao acaso com 24 tratamentos, sendo 20 dispostos no esquema fatorial 2 x 2 x 5 e quatro testemunhas. Os fatores testados foram: volume de calda (100 e 200 L de calda/ha); dosagens reduzidas -75,2 e 112,8 g de fluazifop-p-butil/ha (respectivamente a 40 e 60% da dosagem recomendada); e horário de aplicação (5, 9, 13, 17 e 21 horas). As testemunhas foram aplicadas com a dosagem recomendada (188,0 g do fluazifop-p-butil/ha) e com os volumes de 100 e 200 L de calda/ha, no mato (sem controle das plantas daninhas) e no limpo (plantas daninhas controladas com enxada manual). As principais espécies de plantas daninhas que emergiram na área experimental foram capim-carrapicho (Cenchrus echinatus), que compunha 60% da comunidade infestante; capim-colchão (Digitaria horizontalis), 10%; e capim-pé-de-galinha (Eleusine indica), 30%. Todas as aplicações do herbicida fluazifop-p-butil, nos horários até as 9 horas e a partir das 17 horas, controlaram eficientemente as três espécies de plantas daninhas e foram seletivas para a cultura de soja. Portanto, o uso do herbicida fluazifop-p-butil pode ser otimizado por meio de reduções na dosagem e no volume de calda em aplicações durante os horários com condições ambientais favoráveis à pulverização.
Optimizing Fluazifop-P-Butyl application on postemergence soybeans (Glycine max)
Keywords: herbicida; horário de aplicação; redução de dosagem; redução do volume de calda; controle de plantas daninhas; Herbicide; application times; spray concentration reduction; spray volume reduction; weed control